Genealogie Księgi Rodzaju - Dziadosz, Dariusz (The Biblical Annals, 2015)
Most readers of Scripture do not normally consider genealogies among its more exciting parts. Their virtual dismissal by most lay readers contrasts sharply with biblical scholar’s obsession with them. For the latter, genealogy may be more fascinating than narrative, because of the historical curiosity that most biblical scholars bring to the text. Of the opening eleven chapters of Genesis, two are exclusively dedicated to genealogical concerns - chapter 5 and chapter 10. Chapter 5 traces the genealogical lineage from Adam to Noah. Chapter 10 focuses on the three sons of Noah and their respective descendants, and the place where each of them settled. Similarly to the narrative account, the two lists serve as evidence of God’s blessing upon these antediluvian patriarchs and upon the genealogical line that leads down to Abraham. Such a blessing is manifested in chronological succession (ch. 5) and territorial expansion (ch. 10).